1996
DOI: 10.1063/1.472640
|View full text |Cite
|
Sign up to set email alerts
|

A study on the structure and vibrations of diphenylamine by resonance-enhanced multiphoton ionization spectroscopy and abinitio calculations

Abstract: Laser-desorption jet-cooling has been applied in combination with mass-selective gas-phase spectroscopic techniques to study the structure and low-frequency vibrations of diphenylamine ͑DPA͒. Two-color ͑1ϩ1Ј͒ resonance-enhanced multiphoton ionization has been used to measure the vibrationally resolved excitation spectrum of the S 1 ←S 0 transition in the 305-309 nm region. Ion-dip measurements have been performed to determine the vibrational structure in the electronic ground state. The electronic spectra of D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
(53 reference statements)
2
15
0
Order By: Relevance
“…Based on calculated vibration frequencies, Choi and Kertesz [11] assigned the IR and Raman spectra of diphenylamine. The conclusion of that the N atom has a pyramidal coordination and the phenyl rings are nonequivalent agrees with the results of the experimental data of Boogaarts et al [12] who also performed ab initio calculations with the even larger 6-31G** basis set (including polarization p functions on H atoms). Similar results were also obtained for torsion angles (14.7o and 44.5o) and deviation of the H atom from the CNC plane (20.8o).…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Based on calculated vibration frequencies, Choi and Kertesz [11] assigned the IR and Raman spectra of diphenylamine. The conclusion of that the N atom has a pyramidal coordination and the phenyl rings are nonequivalent agrees with the results of the experimental data of Boogaarts et al [12] who also performed ab initio calculations with the even larger 6-31G** basis set (including polarization p functions on H atoms). Similar results were also obtained for torsion angles (14.7o and 44.5o) and deviation of the H atom from the CNC plane (20.8o).…”
supporting
confidence: 88%
“…Similar results were also obtained for torsion angles (14.7o and 44.5o) and deviation of the H atom from the CNC plane (20.8o). It is interesting to note that the geometry of the first electronically excited state (singlet), obtained in [12], correspond to a molecular conformation of C 2 symmetry with a planar coordination of bonds around the N atom. The nonequivalent orientation of the rings in the ground electronic state of diphenylamine is disputed by Tretiakov and Cable [13] who concluded that the vibrationally allowed electronic spectra of diphenylamine and three its deuterated analogs, obtained in expanded supersonic jet with resonance-enhanced two-photon ionization, better agree with a C 2 molecular geometry both in the ground and first excited singlet electronic state.…”
mentioning
confidence: 99%
“…In the present experiment, the macropulse repetition rate is 5 Hz and the laser bandwidth is typically 0.5%-1.0% of the central frequency. The molecular beam spectrometer, including the two tunable pulsed UV laser systems, is operated at a 10 Hz repetition rate and has been described previously (Boogaarts, von Helden, & Meijer 1996). A scheme of the experimental setup is shown in Figure 1a.…”
Section: Methodsmentioning
confidence: 99%
“…10 While two extended low-frequency vibrational progressions in 62 and 90 cm Ϫ1 modes were observed, indicating that substantial structural changes occurred upon electronic excitation, no detailed structural or vibrational assignments were presented. Later, in conjunction with ab initio calculations and additional spectra of DPA van der Waals clusters, Boogaarts et al 11 presented evidence for a ground state structure of C 1 symmetry in which the central nitrogen atom was in a pyramidal bonding environment. The excited state, however, was calculated to have C 2 symmetry and a planar nitrogen.…”
Section: Introductionmentioning
confidence: 99%